Intervir, um sistema de apoio e gestão à atividade de ergonomia nas empresas - Macedo, Wellington Fernando de (Universidade Federal de São Carlos, 2012)
This research presents how the computer system Intervir, developed by the Simucad Ergo & Ação group, can assist the job of ergonomics teams during the initial Ergonomics Workplace Analysis methodology phases. Special attention is given describing its usability means. Two cases of use are performed and presented. The first one analyzes absenteeism data from a fictitious company and identifies a required ergonomics intervention demand. The second one describes the activity of a daily task and shows how its health risks would been assessed using the developed computer tool. Finally, the results of a questionnaire answered by users of the system show their perception both regarding the Intervir's human-machine interface and the relevance of its existence.
Keywords: Ergonomia; Usabilidade de software; Software de apoio à ergonomia; Ergonomics; Software usability; Software for supporting ergonomics work teams; ENGENHARIAS::ENGENHARIA DE PRODUCAO